«Скінінг» в індустрії комп’ютерних відеоігор - Маслік, Д. Є. (ХНУРЕ, 2025)
This thesis highlights the importance of proper skinning in 3D character creation for games. It examines how well-painted weights ensure smooth, realistic deformations, preventing stiff or unnatural animations that break immersion. The paper discusses the challenges of balancing bone influences, the impact on performance, and the role of tools like Blender, Maya, and 3ds Max in refining weight distribution. Lastly, the thesis highlights best practices for achieving high-quality results efficiently.
Keywords: «Скінінг»; індустрія комп’ютерних відеоігор